Detection of Mycobacterium Species by Targeting esxA, esxB and espC genes in Cattle and Buffaloes - Singh, Sumeet; Narang, Deepti; Chandra, Mudit; Singh, Randhir; Singh, Jaswinder (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Bovine tuberculosis (bTB) is a chronic disease having a potential zoonotic threat and has a huge economic importance due to morbidity, mortality and production losses. bTB is endemic in India and has a worldwide prevalence, therefore there is a need for early diagnostic technique for the eradication of bTB globally. The objective of this study was to diagnose bTB by targeting esxA, esxB and espC genes in the blood of cattle and buffaloes. A total of 223 blood samples were randomly collected from cattle and buffaloes with a history of respiratory distress. The samples were subjected to conventional PCR targeting esxA, esxB and espC genes. A total of 12 samples out of 223 blood samples were found positive for esxA, esxB and espC by conventional PCR. Blood sample can be used for molecular detection of Mycobacterium tuberculosis organisms by targeting esxA, esxB and espC genes.